Biochar: An Option to Maintain Rice Yield and Mitigate Greenhouse Gas Emissions from Rice Fields in Northeast China - Wenjun Dong; Frederick Danso; Ao Tang; Jun Zhang; Youhong Liu; Ying Meng; Xijuan Zhang; Lizhi Wang; Zhongliang Yang (Agronomy)
Crop production is heavily dependent on fertilizers that negatively impact the environment; therefore, research on biochar to improve the soil’s properties and reduce greenhouse gas emissions has intensified over the years. To elucidate rice yield and greenhouse gas emission (GHG) arising from the application of biochar and N fertilizer on paddy soil in Northeast China, a 3-year (2015–2017) field experiment was established. Adopting a split-plot design with three replicates, two nitrogen (N) fertilizer levels in the main plots were designated as follows: 120 kg N ha−1 (N1, 2/3 of N application rate for optimal local rice yield); 180 kg N ha−1 (N2, full N application rate for optimal local rice yield); and four biochar application rates of no biochar (C0, control); 1.0 t ha−1 biochar (C1); 1.5 t ha−1 biochar (C2); and 2.0 t ha−1 biochar (C3) were designated as sub-treatments. The results showed that in 2015, biochar amendment increased GHG emissions while between 2016 and 2017, biochar amendment of 1.5 t ha−1 decreased CH4 emissions, global warming potential (GWP), and greenhouse gasses intensity (GHGI) by 11.3%, 10.9%, and 17.0%, respectively. On average, for the years 2016 and 2017, the N2O fluxes were 17.0% lower in the N2 plots compared to the N1 plots. Biochar amendment of 1.5 t ha−1 recorded an 8.6% increase in rice yield compared to the control. The soil properties of the study site showed that biochar amendment of 1, 1.5, and 2 t ha−1 augmented soil organic matter by 3.3%, 5.3%, and 5.2%, respectively, and soil phosphorus availability by 6.4%, 11.2%, and 22.6%, respectively. The co-application of biochar at 1.5 t ha−1 and 180 kg N ha−1 effectively regulated GHG emissions while maintaining crop yield. Appropriate co-application of biochar with N fertilizer can be adopted for emission reduction and rice yield maintenance while maintaining soil fertility in Northeast China.